(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The traffic volume at intersections has been arising a problem which leads to accidents, conflicts and congestions. An efficient traffic control at intersections helps in reduction of delays of all vehicles and the probability of crashes. The movement of vehicles efficiency is increased by providing traffic signals, roundabouts, channelized islands at an intersection. Signal timing is most important if we use traffic signals in which green time decides the efficiency of movement of vehicles along with pedestrian walk timing. At an intersection, traffic volume studies are done with the movement and classification of vehicles along with the geometric elements of the road. The video graphic method is used to collect the volume of vehicles for every 15-minutes interval and converted into PCU units. Webster’s and IRC code method are used for signal design. Saturation flow, lost times and passenger car units, width of the road are the significant parameters used to optimize the signal timing in planning, design and control of signalized intersection.